Speed technique excelling system in academic basketball - Nesterovskiy, D. I.; Yevstratov, A. A. (Theory and Practice of Physical Culture, 2017)
Modern basketball training systems give a special priority to the high-speed teamwork excelling and reliability improvement tools and methods focused on integrated training of the core competitive fitness components by special game exercises with time limitations to speed up decision-making and improve technical and tactical skills under pressure from opponents; for the player to be able to respond every game situation in the timely and most efficient manner with a special emphasis on fast and due technical and tactical actions under pressure.